2012
DOI: 10.5966/sctm.2012-0021
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Autologous Transplantation of Bone Marrow Stem Cells for Critical Limb Ischemia: Results of the Naples and Pietra Ligure Evaluation of Stem Cells Study

Abstract: Critical limb ischemia (CLI) is a vascular disease affecting lower limbs, which is going to become a demanding challenge because of the aging of the population. Despite advances in endovascular therapies, CLI is associated with high morbidity and mortality. Patients without direct revascularization options have the worst outcomes. To date, 25%–40% of CLI patients are not candidates for surgical or endovascular approaches, ultimately facing the possibility of a major amputation. This study aimed to assess the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 51 publications
2
21
0
1
Order By: Relevance
“…Approximately 18 million Americans have peripheral artery disease (PAD) and 2 million of these patients suffer from critical limb ischemia (CLI), 1,2 the end stage of PAD. 3 CLI is highly prevalent in older patients with diabetes and/or end-stage renal disease 4 and is associated with high risk of amputation and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 18 million Americans have peripheral artery disease (PAD) and 2 million of these patients suffer from critical limb ischemia (CLI), 1,2 the end stage of PAD. 3 CLI is highly prevalent in older patients with diabetes and/or end-stage renal disease 4 and is associated with high risk of amputation and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Although restricted in their differentiation potential, these stem cells possess the capability to self‐renew and give rise to multiple specialized cell types [20], thereby exhibiting remarkably low tumorigenicity [16, 18, 21, 22]. Another advantage of adult stem cells is that their application allows autologous cell transplantation, avoiding the need for long‐term immunosuppression in the patient [2326]. With respect to PD treatment strategies, rat mesenchymal stem cells (MSCs) were recently reported to differentiate into tyrosine hydroxylase‐positive (TH + ) DA neurons in a 6‐hydroxydopamine (6‐OHDA) rat model, accompanied by slight improvement of motor deficits after 8 weeks [27].…”
Section: Introductionmentioning
confidence: 99%
“…Pilot human studies have shown that autologous transplantation of bone marrow cells induced therapeutic angiogenesis in patients with critical limb ischemia [3]. hMSCs are pluripotent progenitors that can differentiate into a variety of cell types and have been shown to promote angiogenesis both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%